Subramanianospora vesiculosa: a hyphomycete causing wilt disease of Casuarina equisetifolia - and D.W. MINTER, C. NARAYANAN, J.K. SHARMA* (Indian Phytopathology, 2003)
The causal organism of wilt or ’blister bark’ disease of Casuarina equisetifolia, identified as a hyphomycete Trichosporium vesiculosum, is described, illustrated and discussed. It is concluded that the fungus cannot satisfactorily be placed in any of the existing genera. Therefore, Subramanianospora gen. novo is proposed with the type species S. vesiculosa.